ANALISIS KELAYAKAN FINANSIAL USAHA AGROINDUSTRI TAHU (Studi Kasus Agroindustri Tahu Bapak Warijan di Desa Rambah Muda Kecamatan Rambah Hilir Kabupaten Rokan Hulu) - Umay Mulyani; Yusmini '; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims to find out and analyze: Financial Feasibility, The level of sensitivity Mr.Warijan’s tahu agro-industry business changes of price levels of material (soybeans) and decrease of production. This research methods using case studies with informant agro-industry businessman. The financial eligibility with the traits of investment criteria: Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Internal Rate of Return (IRR) and Payback Period (PP). The result of the analysis investments criteria period for 10 years, tahu agro-industry business feasible carried out for develop, that is retrieved the value of NPV Rp.420.095.475, Net B/C registration 4 (bigger than 1), IRR is bigger than discount factor 12% that 55% and payback period 4 years with 4 month, it’s mean this business cover the cost of the first investment before the age of business ends. The result of the sensivity the increase in material soybean 10% and the descrease in production scale 10% shows this business not allow implementations, because the value of NPV negative, Net B/C 0, IRR is smaller than discount factor 12% and no payback period, means there is no flow  payback of capital. Based on the result the sensitivity analysis increase value of material soybean, as well as descrease scale of production will making Mr.Warijan’s higlhly influential against feasibility of business or business development tahu agro-industry.   Keywords : Agroindustry, Financial Feasibility, Sensitivity, Tahu